Utilization of Mobile Applications for Digital Marketing of MSMEs: Challenges and Opportunities in Central Lampung - Ferdiansyah, Muhammad; Mariya, Lika; Widyastuti, Widyastuti (Politeknik Harapan Bersama, 2025)
This study aims to identify and recommend the development of a digital marketing application for MSMEs in Central Lampung, with a focus on addressing operational challenges and limited market access. Using the Systems Development Life Cycle (SDLC) approach with the Waterfall method, this research examines the necessary features to improve operational efficiency, expand market reach, and support data-driven decision-making. The key features recommended include a digital product catalog, payment integration, customer notifications, order tracking, and an analytics dashboard. This application is expected to reduce reliance on costly traditional promotional methods, while enhancing product visibility and customer interaction. However, challenges such as low digital literacy and limited internet infrastructure in some areas remain barriers that must be addressed through training, infrastructure improvement, and incentive strategies. The study suggests further research to evaluate the long-term impact and the potential application of advanced technologies to support more personalized and effective marketing strategies for MSMEs.